The Scholarly Knowledge Ecosystem: Challenges and Opportunities for the Field of Information - Altman, Micah; Cohen, Philip N. (Frontiers in Research Metrics and Analytics, 2022)
The scholarly information ecosystem presents an outstanding exemplar of the challenges of understanding, improving, and governing information ecosystems at scale. This article draws upon significant reports on aspects of the scientific information ecosystem to characterize the most important research challenges and promising potential approaches. Across a range of disciplines, we identify reports that are conceived broadly, published recently, and written collectively. We extract the critical research questions, summarize these using quantitative text analysis, and use this quantitative analysis to inform a qualitative synthesis. Three broad themes emerge from this analysis: the need for multi-sectoral cooperation and coordination, for mixed methods analysis at multiple levels, and interdisciplinary collaboration.